The United Nations and the protection of civilians in African conflicts - Hamilton, Leigh (Department of Political Studies, 2014)
Since 1948, the United Nations (UN) has launched 83 peace missions across the globe. After the end of the Cold War, the nature of UN peace missions changed and the UN began to mandate its peace soldiers to perform a greater variety of tasks. One of these tasks was the protection of civilians (POC). While much work has been done on the growth of the civilian protection agenda and the role that peacekeepers play in protecting civilians during armed conflict, these works have been descriptive narratives that lack any sort of theoretical component that conceptualizes POC as a norm. This thesis conceptualizes POC as a norm and utilizes a Constructivist framework based on Martha Finnemore's and Kathryn Sikkink's norm life-cycle in order to identify how the norm of civilian protection during conflict in Africa evolved at the UN, beginning in 1992 and ending in 2011. It argues that the greatest impetus for the evolution of the POC norm came from actors within the UN, who were motivated by organizational survival, even though the institutionalization of normative evolution at the UN did not necessarily lead to the demonstration of POC by UN peace soldiers on the ground. This thesis aims to prove this assertion by applying a Constructivist framework to a case study, which consists of UN peace missions in four different African nations: Somalia, Rwanda, Sierra Leone and Sudan. This thesis also aims to build upon existing Constructivist theory.